2014
DOI: 10.1007/s00520-014-2282-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of professional oral health care on reducing the risk of chemotherapy-induced oral mucositis

Abstract: PurposeRecent years have seen remarkable progress in cancer therapy, although treatment-induced adverse reactions and complications are not uncommon. Approximately 40 % of patients undergoing chemotherapy for cancer experience adverse reactions in the oral cavity, with nearly half of them developing severe oral mucositis that necessitates postponing therapy and/or changing the drug dosage. The objective of this study was to assess the usefulness of prophylactic professional oral health care (POHC) for preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
2
44
1
2
Order By: Relevance
“…A total of 19 articles met the inclusion criteria (See Supporting Information Table 1S). Twelve studies were graded as low‐quality, five as moderate, and two of high quality …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 19 articles met the inclusion criteria (See Supporting Information Table 1S). Twelve studies were graded as low‐quality, five as moderate, and two of high quality …”
Section: Resultsmentioning
confidence: 99%
“…Chen et al . retrospectively divided patients based on the level of dental treatment received in their last year of life.…”
Section: Role Of Professional Dental Servicementioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the Japan Dental Association and the National Cancer Center recommend preventing adverse dental events by means of dental care before and after surgery for cancer patients, thus improving the quality of life for patients undergoing treatment. Moreover, Yoneyama et al reported on the importance of professional oral health care (POHC) for the elderly [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is still no definite method for the treatment and prevention of oral mucositis, various measures, including oral and dental hygiene, 8 different mouthwashes, 9-11 topical anesthetics such as lidocaine, 12 diphenhydramine, 13 nystatin, sucralfate and psychotherapy 12 are currently suggested. In addition, given many complications of stomatitis caused by chemotherapy, its prevention significantly reduces the cost of health care and also increases patient survival, and use of propolis and artificial saliva is among these methods.…”
Section: Introductionmentioning
confidence: 99%